Spirit of Place Study of Malioboro Cultural Heritage Case Study: Margo Utomo Road Section - Fangestu, Ary; Allaisy, Alfaaruq; Agustiananda, Putu Ayu P.; Sholihah, Arif Budi (Universitas Bandar Lampung (UBL), 2025)
Margo utomo is one of the famous street names in Yogyakarta, which is located south of the white pal monument to the eastern entrance of the monument station and is included in the philosophical axis. This research focuses on the margo utomo road section which is included in the Malioboro Cultural Heritage Area (KCB). The urgency of this research is to find the Genius Loci and describe the context that is owned as a public space. The purpose of this research is to explore the city's public space by looking at image expression by finding visual uniqueness, the spaces formed and the character of the area created. This research uses a qualitative descriptive method with an architectural phenomenology approach by describing the Genius Loci that are formed. The results of the research found the role of the philosophical axis as a Genius Loci owned by the road section because it provides local uniqueness in the aspects of image, space and character. This research recommends when the development of road sections is carried out with a phenomenological approach because it strengthens the Genius Loci owned so that it can strengthen the philosophical axis as the main element.